DEVELOPMENT OF VIDEO TUTORIAL LEARNING MEDIA ON WEB PROGRAMMING COURSES USING HANNAFIN AND PECK MODEL - Muhammad Multazam; Zulfiati Syahrial; Rusmono (Journal of Islamic, Social, Economics and Development, 2022)
A web programming course is a course that requires the ability to understand the structure of program code, algorithmic logic, and database processing. Some of the student learning problems are student difficulties. In addition, the data on student learning outcomes is not optimal. Namely, there are 43% of students still have low grades. The solution is to develop video tutorial learning media in web programming courses at the Mataram University of Technology. The research method used in this study is Research and Development with the Hannafin and Peck development model approach. The steps taken are in three stages Needs Assessment, Design, and Development and Implementation. The results showed that the video tutorial learning media developed was feasible to be implemented in learning. This can be seen from the results of the one-to-one evaluation of 91.47%, the small group evaluation of 94.88%, and the field trial results of 92%. Based on students' answers to questions about learning motivation when field trials reached 95.2%, it was found that learning through video tutorials that had been developed could increase students' motivation in learning web programming.